The Effect of Compensation, Work Environment, and Employer Branding on the Interest in Applying for Work of Nusa Putra University Students - Anjani, Meri; Lutfiani, Maulita; Kharisma, Kharisma (Westscience Press, 2025)
This study aims to analyze the influence of compensation, work environment, and employer branding on the job application intention of 8th semester students at Universitas Nusa Putra. Given Generation Z's crucial role in the future workforce and their high turnover rates, understanding the factors influencing their job application interest is vital. Employing a quantitative correlational approach with Proportionate Stratified Random Sampling, the study involved 3,295 students. Results indicate that work environment and employer branding have a positive and significant impact on job application intention, while compensation does not significantly influence it. Simultaneously, the three variables explain 71.8% of the variation in job application intention. These findings underscore the importance for companies to focus on enhancing work environment quality and developing strong employer branding strategies, and for universities to facilitate collaborations with companies excelling in these aspects. This research contributes to understanding Generation Z's work preferences and aids companies in devising more effective recruitment strategies.